Editorial Preface - Ismail, Al Emran; Daud, Zawawi; Ibrahim, Nabilah (International Journal of Integrated Engineering, 2017)
An International Journal of Integrated Engineering (IJIE) is a single blind peer-reviewed journal which publishes three times a year. It is dedicated to promoting three different fields of engineering such as Mechanical and Manufacturing Engineering, Civil and Environmental Engineering & Electrical and Electronic Engineering. Â It is not only published research journals from Malaysia but also attracted people worldwide. Papers from Volume 9, Issue 1 2017 consists of seven papers where three out of seven came from other countries and therefore exchanging knowledge, science and technology for a bright future.Â